Health and wellbeing of the transnet-phelophepa health care train community: a mixed methods case study - Tshabalala, Amme Mardulate (My University, 2016)
„Unhappy people cannot create a society enjoying wellbeing‟ (Alatartseva and Barysheva, 2015:36). This statement in the context of the Transnet-Phelophepa Health Care Train (abbreviated henceforth as the Transnet-Phelophepa HCT) implies the importance of maintaining the health and wellbeing of the service providers who are responsible for the health and wellbeing of society, through the services provided by the train. The service providers consist of two main groups: yearly-contract employees (called „permanent service providers‟) and Health Sciences students working on the train for up to two weeks (called „students‟ in this paper). The focus in this study is on aspects that impact on the health and wellbeing of the Transnet-Phelophepa HCT service providers and service users. King‟s (1981) theoretical framework of conceptual systems is used to discuss the key constructs of health and wellbeing that were researched. Purpose and objectives: The statement of purpose of this study was phrased around several identified facets of health and wellbeing on the Transnet-Phelophepa HCT. Phase 1 The objectives of the study were to collect, determine, describe and explore the following aspects related to working, living and being served by the Transnet-Phelophepa HCT: a) the safety climate as perceived by the health sciences students b) the health sciences students‟ perceptions of decision latitude and social support c) the levels and sources of work stress among permanent service providers d) the permanent service providers‟ perceptions of their quality of life e) the permanent service providers‟ experiences of life f) the opinions of the service users, i.e. members of the public, about the health care they received. Phase 2 Based on the research findings, recommendations were formulated for health and wellbeing on the Transnet-Phelophepa HCT. Methodology: Based on the methodological assumptions, a mixed methods embedded case study design was adopted for this study and implemented in two phases. In Phase 1, a convergent parallel design was applied wherein five quantitative surveys and eight qualitative in-depth interviews were conducted for the purpose of exploring and describing health and wellbeing on the Transnet-Phelophepa HCT. Data collection: Five quantitative surveys were employed. Two of these collected data from a sample of 257 health science students (n=257). The first survey explored their perceptions of the train‟s safety climate and the second survey determined their perceptions of decision latitude and supervisor support. The third and fourth surveys collected data from permanent employees (n=19) to determine their sources of work stress and perceptions of their quality of life on the Transnet-Phelophepa HCT. The fifth survey collected data from a sample of service users (n=124) to explore their perceptions of the health care provided on the Transnet-Phelophepa HCT. A qualitative study exploring permanent employees‟ experiences of life on the Transnet-Phelophepa HCT was conducted using eight in-depth interviews to collect data from participants (n=8) until data saturation was reached. Data analysis: In Phase 2, Onwuegbuzie and Teddlie‟s (2003) seven-stage conceptualisation of the mixed methods data analysis process was applied for the purpose of formulating recommendations for health and wellbeing on the Transnet-Phelophepa HCT. The main findings of the study were constructed within King‟s (1981) conceptual model of interacting systems address the main facets of wellbeing. King‟s interacting systems are defined as the personal, interpersonal and social. Results: The main facets of health and wellbeing emerging from the results include the following: Personal systems are discussed in the context of space. The Transnet-Phelophepa HCT is perceived as a safe environment. However, concerns were raised regarding the possibility of occupational health and safety hazards. Facets related to interpersonal systems are: supervisor support, co-workers‟ relations as perceived by students, as well as permanent employees‟ perceptions of sources of stress on the Transnet-Phelophepa HCT. Social systems are discussed in relation to health care service provision, work/home balance, as well as authority, decision-making and control. Key words: Transnet-Phelophepa, Health Care Train, mixed methods case study, safety climate, job content, decision latitude, work stress, quality of life, health, wellbeing.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2016